The Paradox of Government Spending and Demographics on Central Java's Economic Growth - Wahyu Adi Nugroho; Endah Saptutyningsih; Ahmad Makruf (UNIVED Press, 2026)
This study analyzes the paradoxical relationship between government spending, population, and Gross Regional Domestic Product (GRDP) across 35 districts/cities in Central Java from 2019 to 2023. Using panel data regression and selecting the Fixed Effect Model (FEM) based on the Chow and Hausman tests, this study examines the influence of government spending (PM), life expectancy (UHH), school enrollment rate (APS), and total population (JP). The results indicate that government spending and total population have a negative and significant effect on GRDP, contradicting conventional economic theory. Conversely, life expectancy shows a positive and significant impact, while the school enrollment rate does not demonstrate a statistically significant influence. This paradox highlights the inefficiency of local fiscal allocation and the challenges of demographic management in Central Java. The findings suggest that accelerating regional economic growth requires improving the efficiency of government spending, enhancing the quality of human capital through better health outcomes, and managing population growth in conjunction with labor market expansion.